Lower performance of Toxoplasma-infected, Rh-negative subjects in the weight holding and hand-grip tests - Flegr, Jaroslav; Šebánková, Blanka; Příplatová, Lenka; Chvátalová, Veronika; Kaňková, Šárka (PloS one, 2018)
BACKGROUND: Toxoplasma, a protozoan parasite of cats, infects many species of intermediate and paratenic hosts, including about one-third of humans worldwide. After a short phase of acute infection, the tissue cysts containing slowly dividing bradyzoites are formed in various organs and toxoplasmosis proceeds spontaneously in its latent form. In immunocompetent subjects, latent toxoplasmosis was considered asymptomatic. However, dozens of studies performed on animals and humans in the past twenty years have shown that it is accompanied by a broad spectrum of specific behavioural, physiological and even morphological changes. In human hosts, the changes often go in the opposite direction in men and women, and are mostly weaker or non-existent in Rh-positive subjects. METHODS: Here, we searched for the indices of lower endurance of the infected subjects by examining the performance of nearly five hundred university students tested for toxoplasmosis and Rh phenotype in two tests, a weight holding test and a grip test. RESULTS: The results confirmed the existence of a negative association of latent toxoplasmosis with the performance of students, especially Rh-negative men, in these tests. Surprisingly, but in an accordance with some already published data, Toxoplasma-infected, Rh-positive subjects expressed a higher, rather than lower, performance in our endurance tests. DISCUSSION: Therefore, the results only partly support the hypothesis for the lower endurance of Toxoplasma infected subjects as the performance of Rh-positive subjects (representing majority of population) correlated positively with the Toxoplasma infection.
Keywords: Young Adult; fyzická vytrvalost; protilátky protozoální; Rh-Hr Blood-Group System; Toxoplasma; Immunoglobulin G; Male; Immunoglobulin M; mladý dospělý; imunoglobulin M; Hand Strength; imunoglobulin G; Antibodies, Protozoan; toxoplazmóza; mužské pohlaví; síla ruky; krevní skupiny - systém Rh-Hr; lidé; Physical Endurance; Toxoplasmosis; ženské pohlaví; Humans; Female